2014
DOI: 10.1103/physreva.89.053625
|View full text |Cite
|
Sign up to set email alerts
|

Pinning of hidden vortices in Bose-Einstein condensates

Abstract: We study the vortex dynamics and vortex pinning effect in Bose-Einstein condensate in a rotating double-well trap potential and co-rotating optical lattice. We show that, in agreement with the experiment, the vortex number do not diverge when the rotational frequency Ω → 1 if the trap potential is of anisotropic double-well type. The critical rotational frequency as obtained from numerical simulations agrees very well with the value √ l/l for l = 4 which supports the conjecture that surface modes with angular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The three singly quantized phase defects show that the circular density hole is not a giant vortex. Actually, they are known as singly quantized hidden vortices [15,27,33,46] because they carry significant angular momentum, though they are invisible in the in situ density profile of the BEC. Only after including the hidden vortices can the Feynman rule be satisfied [15,47,48].…”
Section: Steady Structure Of a Rotating Sbfmmentioning
confidence: 99%
“…The three singly quantized phase defects show that the circular density hole is not a giant vortex. Actually, they are known as singly quantized hidden vortices [15,27,33,46] because they carry significant angular momentum, though they are invisible in the in situ density profile of the BEC. Only after including the hidden vortices can the Feynman rule be satisfied [15,47,48].…”
Section: Steady Structure Of a Rotating Sbfmmentioning
confidence: 99%
“…It may be mentioned here that according to Feynman rule < L z >∼ N/2 where N is the number of vortices in the system. If there are both visible and hidden vortices in the condensate then < L z >∼ (N v +N h )/2 where N v and N h denote the total number of visible and hidden vortices respectively in the system [16]. On careful examination we observed that there are three hidden vortices inside the giant hole.…”
mentioning
confidence: 95%
“…The increase in the angular difference |α 1 − α 2 | max show that the vortex lattice gets increasingly distorted with the strength of the impurity potential V 0 (red line). Similarly the impurity potential energy E impurity initially decreases quite rapidly with increasing V 0 (green dots) and finally it attains nearly a constant value showing that the vortex lattice has got pinned to the impurity [16]. It is known that a 'giant hole' created in BEC can be used to study controlled circular superflow and phase slippage in superfluids and also the transverse Tkachenko modes in the vortex lattice [43].…”
mentioning
confidence: 99%
See 2 more Smart Citations